Evaluating an Alternative to the Emergency Department for Adults in Mental Health Crisis. (3rd July 2017) - Heyland, Michelle; Johnson, Mary
ABSTRACT: Adults with mental health issues lack clinically indicated options when in crisis. Historically, the emergency department (ED) has been the primary source of intervention largely due to funding cuts and decreased community resources in the USA. The literature highlights drastic mental health funding cuts alongside an increased prevalence of mental illness. A community-based alternative for adults in mental health crises was subsequently developed as a model of crisis care. The program has demonstrated impressive short-term outcomes, typically avoiding ED admissions in over 95% of the clients. This number benefits both the consumers who otherwise rely on the ED and the State of Illinois in terms of cost savings for avoidable ED visits. The current deflection rate only reflects ED admissions deflected on the day of the visit to the crisis respite program. To establish the long-term outcomes for this model, follow-up phone calls were conducted to determine whether or not the individual required an ED visit for a psychiatric reason within 30 days of utilization of the program. The follow-up phone calls began in May and continued for eight weeks. At this time, the data collected were analyzed and the outcomes of the program were further evaluated. Based on the follow-up survey results, the positive long-term outcomes validate this model as a cost-saving and clinically indicated alternative to the ED. Establishing such outcomes was necessary to ensure continued funding and to support establishment of similar models of crisis care.